1997
DOI: 10.1139/bcb-75-4-427
|View full text |Cite
|
Sign up to set email alerts
|

A nuclear factor other than Sp1 binds the GC-rich promoter of the gene encoding rat poly(ADP-ribose) polymerase in vitro

Abstract: Poly(ADP-ribose) polymerase is a nuclear enzyme that has been shown to exert a key role in many important cellular functions, including DNA repair. Its activity was shown to vary substantially between tissues; the testis and the thymus expressed the highest levels of PARP whereas the liver and the kidney (as well as a few other tissues) expressed only low levels of PARP proteins in vivo. The GC-rich nature of its upstream gene promoter, along with the lack of TATA and CAAT boxes, a feature common to most house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…A detailed examination of the DNA sequence from the ␣ 5 FRE indeed revealed the presence of a perfect half-palindromic site for NF1 (TGGCA; see Figs. 2B and 10) that has been previously reported to bind this transcription factor (44,45).…”
Section: Methodsmentioning
confidence: 86%
“…A detailed examination of the DNA sequence from the ␣ 5 FRE indeed revealed the presence of a perfect half-palindromic site for NF1 (TGGCA; see Figs. 2B and 10) that has been previously reported to bind this transcription factor (44,45).…”
Section: Methodsmentioning
confidence: 86%
“…Mean AE SD of three independent experiments. transcription factors such as Sp1, Sp3 (32), and NF1 (33). However, the increase in PARP1 protein in nasopharyngeal carcinoma was unlikely to be due to an increase in transcription because no significant variation in PARP1 mRNA between nasopharyngeal carcinoma and nasopharyngeal epithelial cell lines was observed (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…37) or the target sequence for human HeLa CTF/NF-I (5Ј-GATCTTATTTTGGATGAAGCCAATATG-AG-3Ј; Ref. 42) were 5Ј-32 P-end-labeled as described previously (43) and used as probes.…”
Section: Methodsmentioning
confidence: 99%
“…3 The human promoter has been shown to contain binding sites for transcription factors Sp1, AP-2 (30), YY1 (32), and Ets (33), whereas the mouse promoter was recently shown to be down-regulated by a complex of adenovirus E1A protein and pRb (34). In the case of the rat PARP-1 (rPARP) proximal promoter, we have shown that it is highly but not completely dependent on five Sp1 binding sites (35,36), and that other nuclear proteins, including one likely belonging to the nuclear factor 1 (NF1) family of transcription factors (37), bind to and potentially regulate rPARP promoter transcription.…”
mentioning
confidence: 92%